Triple bothropic envenomation in horses caused by a single snake - Chiacchio, S. B. [UNESP]; Martins, G. T. B. [UNESP]; Amorim, R. M. [UNESP]; Goncalves, R. C. [UNESP]; Barraviera, Benedito [UNESP]; Ferreira Júnior, Rui Seabra [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
In the present study, snakebites caused by a single Bothrops pauloensis simultaneously affecting three male adult horses are described. Whereas the first two affected horses were six years old, the third was 16 years old; they weighed respectively 555, 550 and 500 kg. All horses presented swollen muzzles. The first animal received an initial antivenom dose of 19 vials and adjuvant medication, it was also subjected to tracheostomy due to the progression of acute respiratory failure. The second and third horses respectively received 15 vials of antivenom each, in addition to adjuvant medication. Due to continuous changes in blood coagulation observed during hospitalization, the first and the second horses received five more vials of antivenom, respectively, in the second and third days of treatment. The first animal was discharged on 15(th) day and the other on the 8(th) day of hospitalization. Several factors including the main actions of Bothrops venom (coagulation, proteolytic and vasculotoxic activities), the importance of early diagnosis based on clinical history and clinical examination suggesting the diagnosis of Bothrops snakebite, the adequate doses of antivenom, and finally the immediate tracheostomy are herein discussed. The tracheostomy, required to save the life of the first horse, should only occur after the administration of antivenom and control measures for changes in blood coagulation.
Keywords: Bothrops; snakebite; equine; antivenom; tracheostomy